Numerical Simulation and Validation of Aerosol Particle Removal by Water Spray Droplets With OpenFOAM During the Fukushima Daiichi Fuel Debris Retrieval - Liang, Hui; Erkan, Nejdet; Solans, Virginie; Suzuki, Shunichi (Frontiers in Energy Research, 2020)
In the decommissioning of damaged Fukushima Daiichi reactors, the melted and re-solidified fuel debris in the bottom of the reactor pressure vessel and primary containment vessel need to be cut into small pieces before removing them from reactor buildings. During the cutting operations, submicron radioactive aerosol particles are expected to be generated and dispersed into the atmosphere of the primary containment vessel. Those suspended particles must be removed from the air atmosphere inside the containment before escaping to the environment. The water spray system in the upper part of the primary containment vessel is an effective and applicable method to remove airborne radioactive aerosol particles. Computational Fluid Dynamics simulation of aerosol scavenging by spray droplets is complicated but necessary to investigate the aerosol removal process inside the vessel. In this paper, a numerical model was developed and implemented into an open-source computational fluid dynamic code OpenFOAM to simulate the aerosol removal by water spray droplets with considering the collection mechanisms of inertial impaction, interception, and Brownian diffusion. In this model, the dispersed spray droplets were described using the Lagrangian particle tracking method, the continuous particle-laden gas was described using the Eulerian method, and a two-way interaction between dispersed and continuous phases was considered. The polydisperse aerosol particles at different diameters from 0.2 to 1 μm were treated as different gas species of the continuous phase. Continuity equations of each gas specie were solved using a passive scalar transport equation. The numerical model was validated by comparing the simulation results with the experimental data obtained from UTARTS facility. Simulation results agreed well with the experimental results. The simulation results provided more insights to better understand the aerosol removal process, including the time evolution of aerosol mass fraction and flow field of the gas phase.